Audience Heterogeneity and the Effectiveness of Market Signals: How to Overcome Liabilities of Foreignness in Film Exports? - Kim, Heeyon; Jensen, Michael (Academy of Management Journal, 2014)
This study extends research on the importance of market signals in international markets for cultural products by examining not only when market signals are important but also what types of market signals are most important to which audiences. Specifically, we argue that audience heterogeneity influences the effectiveness of commercial performance and artistic acclaim as market signals in international film markets. Audience heterogeneity refers to the differences in the cultural knowledge and preferences of domestic and foreign consumers (end audiences) and product specialization of domestic and foreign distributors (intermediary audiences). Our empirical setting is the European film industry. We use a large sample of films produced and distributed domestically and internationally in Europe between 2004 and 2009. We find that domestic commercial performance and film festival participation increase international film success, but also that their effects depend on the cultural distance between countries and the use of major or independent distribution in the domestic and foreign markets.